Cover Picture: Light‐Activated Antibacterial Nanoscale Films: Metallo‐Organics for Catalytic Generation of Chemically Accessible Singlet‐Oxygen in Water (ChemistrySelect 2/2017). Issue 2 (13th January 2017) - Morozov, Michael; Carmieli, Raanan; Lahav, Michal; van der Boom, Milko E.
Abstract : The cover picture shows how metallo‐organic materials can be applied as antibacterial coatings by using environmental samples. The robust and reusable nanoscale films generate catalytically reactive oxygen species under light. Our observations also indicate that the photo‐responsive nanoscale coatings can potentially be used for both the elimination of bacteria and the oxidation of harmful organics in water. More information can be found in the Communication by Lahav and van der Boom et al. (DOI: 10.1002/slct.201601724 ). (Design: Tali Wiesel).